Polyimide with high surface electric strength based on surface natural microporous structure regulation and control as well as preparation method and application of polyimide
By regulating the natural microporous structure on the surface of the polyimide, the problem of low electrical resistance strength along the side of the polyimide in the vacuum insulation system is solved, and a significant increase in electrical resistance strength and a reduction in dielectric constant are achieved, which is suitable for insulated components of high-energy equipment.
Patent Information
- Application Number
- CN202411703934.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-26
AI Technical Summary
Polyimide has low electrical resistance along the side in vacuum insulation systems and is prone to flashover along the side, limiting the development of high-energy equipment.
By regulating the natural microporous structure on the surface of the polyimide, adding a pore-forming agent and preparing it by high-temperature heating or liquid extraction, polyimide with a dense micron-scale pore structure is formed.
It effectively suppresses the development of secondary electron collapse, significantly improves the electrical resistance of polyimide along the surface, and reduces the dielectric constant, and is suitable for insulated components of high-energy equipment.
Smart Images

Figure CN119505355A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of high voltage insulating materials, and in particular relates to a polyimide with high surface electrical strength regulated by natural microporous structure on the surface, and a preparation method and application thereof. Background Art
[0002] As a new generation of thermoplastic polymer materials with natural rigid chains, polyimide has excellent comprehensive properties such as high and low temperature resistance, high mechanical strength, wear resistance, radiation resistance, good chemical stability and dielectric properties. It has high commercial value and has been widely used in key fields such as electrical insulation, microelectronics industry, atomic energy, aerospace, etc. However, in vacuum insulation systems, the surface dielectric strength of polyimide is much lower than its own breakdown strength, and it is very easy to discharge along the surface of polyimide, that is, surface flashover. This problem has become one of the key technical bottlenecks restricting the development of spacecraft, pulse power equipment, high-energy particle accelerators, semiconductor manufacturing and processing equipment towards high power, miniaturization and integration. Therefore, the development of a polyimide with high surface dielectric strength is of great significance to improving the insulation reliability and safety of industrial systems.
[0003] Vacuum surface flashover is a low-pressure plasma discharge phenomenon along the surface of a solid medium caused by a secondary electron avalanche. The process can be divided into the initial stage (cathode field-induced electron emission), the development stage (secondary electron multiplication) and the breakdown stage (gas desorption ionization and breakdown). Therefore, to improve the surface dielectric strength of polyimide in a vacuum, it is necessary to suppress the development of at least one stage. Based on this theory, domestic and foreign researchers have proposed many suppression methods. Patent CN105405545B achieves the purpose of adjusting the secondary electron emission multiplication process of the insulator by mechanically machining grooves on the surface of the insulator and embedding electrodes in the grooves. However, this solution is complex and expensive, and it is difficult to achieve large-scale industrial production and application. Patent CN115910497A uses 3D printing technology to obtain an insulator with multiple through holes on the surface and inside, so that electrons pass through the through holes and fall into the cavity during the flashover process, thereby suppressing the secondary electron avalanche and improving the surface dielectric strength of the insulator. However, the 3D printing process is complicated, and the polyimide material, especially the polyimide film preparation process, is not suitable for preparation by 3D printing. Therefore, this scheme is not suitable for the preparation of highly surface-resistant polyimide. At present, there are also methods of using matrix nanocomposite modification and surface treatment (such as fluorination, plasma treatment, composite coating, plating, etc.) to achieve the suppression of surface flashover, but these methods have little suppression effect and are prone to failure. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface, and a preparation method and application thereof, so as to solve the technical problem of how to effectively inhibit the development of secondary electron avalanche by regulating the natural microporous structure on the surface of polyimide, thereby improving its surface dielectric strength.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a preparation method of a polyimide with high surface dielectric strength regulated by natural microporous structure on the surface, comprising: dissolving a dried diamine in a solvent A, adding a dianhydride, and stirring evenly to obtain a polyamic acid solution; adding a pore-forming agent, stirring at high speed until uniform dispersion to obtain a mixed viscous solution C; coating, drying, imidization, high-temperature heating, and natural cooling, immersing in a liquid B to extract the pore-forming agent, and drying to obtain the polyimide with high surface dielectric strength regulated by natural microporous structure on the surface.
[0006] Preferably, the molar ratio of dianhydride to diamine is (0.98-1.05):1; When adding dianhydride, add it in small amounts and multiple times, with an interval of 15-30 minutes between each addition. Stirring under nitrogen or air atmosphere until a uniform yellow transparent polyamic acid solution is formed; The solid content of the polyamic acid solution is 15-20 wt %.
[0007] Preferably, the diamine is one or more of 4,4'-diaminodiphenyl ether, p-phenylenediamine, 4,4'-diaminobiphenyl, 2,2'-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminophenyl sulfone, hexamethylenediamine, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 4,4'-(4,4'-isopropylidene diphenyl-1,1'-diyldioxy)diphenylamine and related derivatives thereof.
[0008] Preferably, the dianhydride is one or more of pyromellitic dianhydride, 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-phenylenedioxydiphthalic anhydride, 4,4'-biphenyl ether dianhydride and related derivatives thereof.
[0009] Preferably, solvent A is any one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone; liquid B is ethanol or ketone; and liquid B can fully dissolve the pore former without destroying or dissolving the polyimide.
[0010] Preferably, the pore-forming agent is any one of didodecyldimethylammonium bromide, dibutyl phthalate, glycerol, polyethylene glycol, polyethylene oxide and polyhedral oligomeric silsesquioxane; The mass of the pore-forming agent is 5%-40% of the mass of the mixed viscous solution C; When the thermal decomposition temperature of the pore-forming agent is not higher than 440°C, the imidization is heated at high temperature and then cooled naturally to obtain a polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface; When the thermal decomposition temperature of the pore-forming agent is higher than 440°C, the imidization is heated at high temperature, cooled naturally, and then immersed in liquid B to extract the pore-forming agent. After drying, a polyimide with high surface electrical strength based on the natural microporous structure on the surface is obtained.
[0011] Preferably, the speed of high-speed stirring is 800-1400 rpm; and the time of high-speed stirring is 0.5 h.
[0012] Preferably, the high-temperature heating for imidization adopts a gradient heating and heat preservation method, starting from 80°C, at a heating rate of 5°C / min, heat treatment is performed at intervals of 60°C for 40 minutes, the temperature is increased to 300-450°C, heat treatment is performed for 6 hours, and cooling is performed to room temperature; if the thermal decomposition temperature of the pore-forming agent is not higher than 440°C, the thermal decomposition temperature of the pore-forming agent plus 10°C is set as the maximum temperature.
[0013] The present invention also discloses a polyimide with high surface electrical strength regulated by natural microporous structure on the surface, which is prepared by the above-mentioned preparation method. The surface of the polyimide with high surface electrical strength regulated by natural microporous structure on the surface is a surface along the electric field, and the surface along the electric field is densely covered with micron-sized pore structures.
[0014] The present invention also discloses the use of the high surface electrical strength polyimide obtained by the above preparation method based on the regulation of the natural microporous structure on the surface in the preparation of insulating components for spacecraft, vacuum circuit breakers, high-energy particle accelerators, pulse power equipment and semiconductor manufacturing and processing equipment.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The invention discloses a method for preparing a polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface. The polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface is prepared by adding a pore-forming agent component to a precursor polyamic acid solution, and then undergoing basic chemical methods such as imidization, high-temperature heating or liquid extraction. The surface has a pore structure, and the surface is a surface along the electric field. When an electric field is applied to the surface of the polyimide, since there is a through-hole structure on the surface of the polyimide along the electric field, the primary electrons generated by the cathode and the secondary electrons generated during the development process will fall into the through-holes in the process of moving toward the anode, and the interior of the polyimide is also a porous structure. It is difficult for the electrons that fall into the through-holes to escape from the porous structure, and it is even more difficult to return to the surface from the through-holes, thereby achieving the purpose of suppressing the secondary electron collapse. Structurally, the natural through-holes on the surface of the polyimide can capture the electrons of the electron collapse that develops toward the anode along the direction of the electric field during the flashover development process. The electrons that fall into the through-holes are difficult to return to the surface, so as to weaken the development of the electron collapse, and finally significantly improve the vacuum surface dielectric strength of the polyimide. At the same time, since the surface and interior of polyimide are porous, its dielectric constant is significantly lower than that of ordinary polyimide resin, showing better application advantages in the fields of communications and microelectronics. Since the natural polyimide with a microporous structure on the surface is directly prepared, the preparation process is simple and convenient, and it can be formed in one step, which is very suitable for large-scale mass production in industrial production lines. The use of pore-forming agent components of different sizes, contents, and concentrations can achieve the regulation of pore size and porosity. This method can select appropriate pore-forming agents and ratios according to industrial needs, control the degree of development of secondary electron avalanches, and regulate the surface electrical strength of polyimide.
[0016] The present invention also discloses a polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface obtained by the above-mentioned preparation method. The surface of the polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface is densely covered with micron-sized pore structures along the electric field. During the flashover process, electrons are easy to fall into the pore structures during the jump multiplication process, and it is difficult to return to the surface of the polyimide. The secondary electron multiplication process is suppressed, and the probability of forming a secondary electron collapse is reduced, thereby achieving an improvement in the surface dielectric strength of the polyimide. The surface microporous structure size of the polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface is in the micron order. If the opening size of the through hole is too small, the probability of the electrons in the electric field falling into the through hole becomes smaller, and the electrons bypass the through hole and cannot fall into it, so the effective suppression of the secondary electron collapse cannot be achieved. If the opening size of the through hole is too large, the mechanical strength of the polyimide will be destroyed, and the industrial applicability of the polyimide will be reduced.
[0017] The present invention also discloses the use of the high surface dielectric strength polyimide based on the natural microporous structure on the surface obtained by the above-mentioned preparation method in the preparation of insulating components of spacecraft, vacuum circuit breakers, high-energy particle accelerators, pulse power equipment, and semiconductor manufacturing and processing equipment. Spacecraft operate in extreme space environments and have extremely high requirements for insulating materials. The high surface dielectric strength polyimide based on the natural microporous structure on the surface of the present invention can effectively suppress secondary electron collapse due to its surface microporous structure, significantly improve the electrical resistance of the material in vacuum and radiation environments, thereby ensuring the stability and reliability of the electrical system of the spacecraft. In addition, its lower dielectric constant also helps to reduce the loss during signal transmission and improve communication efficiency. The vacuum circuit breaker is a key protection device in the power system, and its performance directly affects the safe and stable operation of the power grid. The use of the high surface dielectric strength polyimide based on the natural microporous structure on the surface of the present invention as an insulating component can significantly improve the breaking capacity and arc resistance of the circuit breaker, extend the service life, and reduce maintenance costs. At the same time, the porous structure also helps to dissipate heat and improve the thermal stability of the equipment. In high-energy particle accelerators, insulating components need to withstand extremely high electric field strengths and radiation doses. The high-surface dielectric strength polyimide based on the regulation of the natural microporous structure on the surface of the present invention, with its excellent electrical resistance and radiation resistance, can ensure the stability and safety of the accelerator under long-term high-load operation, and provide strong support for scientific research and technological applications. Pulse power equipment is widely used in military, scientific research and other fields, and its insulating components need to withstand extremely short pulse high voltage and strong current. The high-surface dielectric strength polyimide based on the regulation of the natural microporous structure on the surface of the present invention, due to its special microporous structure, can effectively inhibit the development of electron collapse, improve the dielectric strength and reliability of the insulating components, and ensure the stable operation of the pulse power equipment. In the semiconductor manufacturing process, the purity and electrical resistance of the insulating components are crucial. The high-surface dielectric strength polyimide based on the regulation of the natural microporous structure on the surface of the present invention not only has excellent electrical resistance, but also its porous structure helps to adsorb and fix impurities and improve the purity of the material. In addition, its lower dielectric constant also helps to reduce signal interference between semiconductor devices and improve integration and performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the structure of a polyimide with high surface electrical strength regulated by natural microporous structure on the surface provided by the present invention; Figure 2 This is a flow chart of a method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface provided in Example 1 of the present invention; Figure 3 This is a SEM microscopic morphology of the surface of the high surface electrical strength polyimide based on the regulation of the natural microporous structure on the surface according to Example 1 of the present invention. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0020] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0021] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional commercial channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials described in this patent are for demonstration purposes only.
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings: According to one aspect of the present invention, a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface is provided. The polyimide is prepared by adding a pore-forming agent component to a precursor polyamic acid solution and then subjecting the polyimide to basic chemical methods such as high-temperature heating through imidization or liquid extraction. The surface of the polyimide has a porous structure, and the surface is along the electric field.
[0023] Specifically, the preparation method of the polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface provided by the present invention is simple, and a pore-forming agent is added to the precursor polyamic acid solution, and then the pore-forming agent is thermally decomposed by high-temperature heating or the pore-forming agent is extracted by solvent to prepare a porous polyimide material with a surface densely covered with through-hole structures. When an electric field is applied to the surface of the polyimide, since there are through-hole structures along the surface of the polyimide in the electric field, the primary electrons generated by the cathode and the secondary electrons generated during the development process will fall into the through-holes in the process of moving toward the anode, and the interior of the polyimide is also a porous structure, and the electrons that fall into the through-holes are difficult to escape from the porous structure, and it is even more difficult to return to the surface from the through-holes, thereby achieving the purpose of suppressing the collapse of secondary electrons, and finally obtaining a polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface.
[0024] Optionally, the thickness of the high surface electrical strength polyimide regulated by the natural microporous structure on the surface is not fixed, and preferably, the thickness is within the range of 25-250 μm of commonly used insulating materials in industry.
[0025] Optionally, the size of the surface microporous structure is determined by the size and content of the added solid pore-forming agent or the concentration and content of the added liquid pore-forming agent, thereby achieving controllable regulation of the surface micropores. The size of the microporous structure on the surface of polyimide is in the order of nanometers and micrometers. Preferably, the size of the microporous structure on the surface of polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface is in the order of micrometers. If the opening size of the through hole is too small, the probability of electrons in the electric field falling into the through hole becomes smaller, and the electrons bypass the through hole and cannot fall into it, so the effective suppression of secondary electron avalanche cannot be achieved. If the opening size of the through hole is too large, it will destroy the mechanical strength of the polyimide and reduce the industrial applicability of the polyimide.
[0026] Optionally, the polyimide matrix is a polyamic acid solution obtained by polycondensation acylation of diamine and dianhydride in solvent A.
[0027] Optionally, the diamine is selected from one or more of 4,4'-diaminodiphenyl ether (ODA), p-phenylenediamine (PDA), 4,4'-diaminobiphenyl (BPA), 2,2'-bis(4-aminophenyl)hexafluoropropane (6FAP), 4,4'-diaminophenyl sulfone (DDS), hexamethylenediamine (HMDA), 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane (6F-BAPP), 4,4'-(4,4'-isopropylidene diphenyl-1,1'-diyldioxy) diphenylamine (IDDA) and related derivatives; The dianhydride is selected from one or more of pyromellitic dianhydride (PMDA), 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-(hexafluoroisopropylene) diphthalic anhydride (6FDA), 4,4'-phenylenedioxydiphthalic anhydride (HQDA), 4,4'-diphenyl ether dianhydride (ODPA) and related derivatives thereof; The solvent A is selected from any one of N,N-dimethylacetamide (DMAc), N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP).
[0028] Optionally, the pore-forming agent is a liquid or solid chemical substance that is insoluble in the polyamic acid solution and does not react with it. Preferably, the pore-forming agent is selected from didodecyl dimethyl ammonium bromide (DDAB), dibutyl phthalate (DBP), glycerol (Gly), polyethylene glycol (PEG), polyethylene oxide (PEO) or polyhedral oligomeric silsesquioxane (POSS) and the like.
[0029] Optionally, liquid B is ethanol or ketone; liquid B can fully dissolve the pore former, and liquid B will not damage or dissolve the polyimide part; the amount of liquid B added ensures that the polyimide can be completely immersed.
[0030] According to another aspect of the present invention, there is provided a method for preparing a polyimide with high surface dielectric strength based on the regulation of the natural microporous structure on the surface, comprising the following steps: Step 1: sublime the diamine and dianhydride in a vacuum drying oven before use; Step 2: Weigh dianhydride and diamine using an analytical balance so that the molar ratio of dianhydride to diamine is (0.98-1.05): 1, add diamine into a three-necked flask, weigh solvent A and pour it into the three-necked flask, stir evenly, and after the diamine is completely dissolved, add dianhydride into the three-necked flask in multiple times, each time interval is 15-30 minutes, and then stir under nitrogen or air atmosphere until a uniform yellow transparent polyamic acid solution is formed, and the solid content of the polyamic acid solution should be 15-20 wt%; Step 3: Weigh a certain amount of pore-forming agent component using an analytical balance, add it to the polyamic acid solution obtained in step 2, and then stir it at a high speed of 800-1400 rpm for 0.5 h under vacuum conditions using a stirrer to uniformly disperse the pore-forming agent component in the polyamic acid solution, thereby obtaining a mixed viscous solution C. The amount of the pore-forming agent used is 5%-40% of the sum of the mass of the pore-forming agent and the polyamic acid solution; that is, the mass of the pore-forming agent is 5%-40% of the mass of the mixed viscous solution C; Step 4: Take the mixed viscous solution C obtained in step 3, spread it on a clean glass plate, apply film with a scraper using a vacuum coating machine, then place it in a vacuum drying oven for drying, and then place it in a high-temperature drying oven to complete high-temperature heating for imidization; Step 5: After natural cooling, take out the polyimide material and immerse it in liquid B to extract the dispersed phase - the pore-forming agent component. Finally, dry it to obtain a polyimide with high surface electrical strength based on the natural microporous structure of the surface. Liquid B is ethanol or ketone. The amount of liquid B is not limited, but it is required to ensure that the polyimide is completely immersed, and liquid B can fully dissolve the pore-forming agent without destroying and dissolving the polyimide.
[0031] Specifically, the initial liquid volume in step three and step four can be selected according to actual needs. If a large membrane area is required, more solution is taken; otherwise, less solution is taken.
[0032] Specifically, in step 4, the high-temperature imidization adopts a gradient heating and heat preservation method, starting from 80°C, heat treatment is performed at intervals of 60°C (140, 200, 260, ...) for 40 minutes until the required maximum temperature is reached, and then heat treatment is performed for 6 hours and then cooled to room temperature. The heating rate during the whole process is 5°C / min, and the maximum temperature should not exceed 450°C. If the thermal decomposition temperature of the pore-forming agent component is not higher than 440°C, the thermal decomposition temperature of the pore-forming agent plus 10°C is set as the maximum temperature; otherwise, the maximum temperature value does not exceed 450°C and is not lower than 300°C.
[0033] Specifically, step five is an optional step. If the thermal decomposition temperature of the pore-forming agent component is not higher than 440°C, the high surface electrical strength polyimide based on the regulation of the natural microporous structure on the surface can be obtained through step four; if the thermal decomposition temperature of the pore-forming agent component is higher than 440°C, step five must be completed, that is, using liquid B to extract the pore-forming agent component.
[0034] Specifically, the above preparation method is first dried in a vacuum oven for a period of time after coating, one is to remove the gas mixed on the surface and inside of the polyamic acid film, and the other is to thermally cure the polyamic acid composite film so that it maintains its shape in the subsequent process, laying the foundation for the material to have good mechanical and insulation properties.
[0035] According to another aspect of the present invention, the present invention also provides the above-mentioned high surface electrical strength polyimide based on the regulation of natural surface micropore structure or the high surface electrical strength polyimide based on the regulation of natural surface micropore structure prepared by the above-mentioned preparation method, and its application in high-energy particle accelerators, spacecraft, vacuum circuit breakers, pulse power equipment and insulating components in semiconductor manufacturing and processing equipment.
[0036] Figure 1Schematic diagram of the structure of the polyimide with high surface electrical strength regulated by the natural microporous structure on the surface provided by the present invention; Figure 1 As shown, the high surface dielectric strength polyimide based on the regulation of the natural microporous structure on the surface appears as an opaque yellow film due to the porous structure.
[0037] Example 1 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: 1) Weigh PMDA and ODA at a molar ratio of 1.02:1, measure DMAc and pour it into a three-necked flask, then add ODA and stir evenly. After ODA is completely dissolved, add PMDA into the three-necked flask four times, each time with an interval of 15 min, and stir until a uniform yellow transparent polyamic acid (PAA) solution is obtained, so that the solid content of the polyamic acid solution is 20 wt%; 2) Add a certain amount of pore-forming agent dibutyl phthalate (DBP) to the PAA solution obtained in step 1) to make the mass percentage of DBP 25%, stir at 800 rpm for 0.5 h to ensure that DBP is evenly dispersed, and apply a film on a clean glass plate with a scraper; 3) The wet film is placed in a vacuum oven for vacuum treatment at room temperature for 2 h, and then placed in a high-temperature forced air drying oven for imidization. The gradient heating process is as follows: heating to 80°C, 140°C, 200°C, 260°C, and 320°C at a rate of 5°C / min, and keeping warm for 40 min at each temperature stage, and finally heating to 350°C and keeping warm for 6 h, and finally cooling to room temperature for demolding, thereby obtaining a polyimide with high surface electrical strength regulated by the natural microporous structure on the surface.
[0038] Figure 2 It is a flow chart of the preparation method of polyimide with high surface dielectric strength based on the regulation of natural microporous structure on the surface provided by Example 1 of the present invention; as can be seen from the figure, a polyamic acid (PAA) solution is first prepared as the basis of the preparation process. A pore-forming agent is added to the PAA solution to regulate the microporous structure on the surface of the polyimide film. The mixed solution is evenly coated on the substrate to form a film. The coated film is placed in a vacuum environment to remove internal bubbles to ensure the uniformity and density of the film. The imidization temperature is determined according to whether the thermal decomposition temperature T of the pore-forming agent is greater than 440°C. If T is greater than 440°C, the maximum imidization temperature is set to T+10°C; if T is not greater than 440°C, 350°C is set for thermal imidization. After thermal imidization, the film is immersed in solvent B to extract the pore-forming agent to form the desired microporous structure. Finally, the film is peeled off from the substrate and dried to obtain a polyimide with high surface dielectric strength having a natural microporous structure on the surface.
[0039] Figure 3This is a SEM microscopic morphology of the surface of the high-along-surface electrical strength polyimide based on the regulation of the natural microporous structure on the surface in Example 1 of the present invention; the thickness was tested by a professional thickness gauge, and it was found that the thickness of the high-along-surface electrical strength polyimide based on the regulation of the natural microporous structure on the surface was 53.86 μm.
[0040] Example 2 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 2 has the same steps as those of Example 1, except that the amount of dibutyl phthalate (DBP) used in step 2) is different, so that its content accounts for 10%, and the remaining steps are the same.
[0041] Example 3 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 3 is the same as that of Example 1, except that the amount of dibutyl phthalate (DBP) used in step 2) is different, so that its content accounts for 20%, and the remaining steps are the same.
[0042] Example 4 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 4 is the same as that of Example 1, except that the amount of dibutyl phthalate (DBP) used in step 2) is different, so that its content accounts for 30%, and the remaining steps are the same.
[0043] Example 5 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 5 is the same as that of Example 1, except that in step 3), the maximum heating temperature is 320° C. and the temperature is kept for 6 h, and the remaining steps are the same.
[0044] Example 6 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 6 is the same as that of Example 1, except that in step 1), the molar ratio of PMDA to ODA is 1.05:1, and the remaining steps are the same.
[0045] Example 7 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 7 has the same steps as those of Example 1, except that in step 1), the molar ratio of PMDA to ODA is 0.98:1, and the remaining steps are the same.
[0046] Example 8 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 8 is the same as that of Example 1, except that the pore-forming agent used in step 2) is polyhedral oligomeric silsesquioxane (POSS), and the remaining steps are the same.
[0047] Example 9 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 9 is the same as that of Example 1, except that the pore-forming agent used in step 2) is polyethylene glycol (PEG), and the remaining steps are the same.
[0048] Example 10 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 10 is the same as the method steps of Example 1, except that in step 1), BTDA and PDA are weighed in a molar ratio of 1.02:1, and after step 3), the polyimide film is taken out and immersed in ketone for 12 hours, and then dried to obtain a polyimide with high surface electrical strength regulated by the natural microporous structure on the surface.
[0049] Embodiment 11 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 11 is the same as that of Example 1, except that, in step 1), BPDA and BPA are weighed in a molar ratio of 1:1, DMAc is measured and poured into a three-necked flask, and then BPA is added and stirred evenly. After BPA is completely dissolved, BPDA is added to the three-necked flask four times, each time with an interval of 30 minutes, and stirred until a uniform yellow transparent polyamic acid (PAA) solution is obtained, so that the solid content of the polyamic acid solution is 15 wt%; in step 3), the maximum heating temperature is 300°C, and it is kept warm for 6 hours.
[0050] Example 12 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 12 is the same as that of Example 1, except that, in step 1), 6FDA and 6FAP are weighed at a molar ratio of 0.99:1, DMAc is measured and poured into a three-necked flask, and 6FAP is added and stirred evenly. After 6FAP is completely dissolved, 6FDA is added to the three-necked flask four times, each time at an interval of 20 minutes, and stirred until a uniform yellow transparent polyamic acid (PAA) solution is obtained, so that the solid content of the polyamic acid solution is 18 wt%; in step 3), the maximum heating temperature is 450°C, and the temperature is kept for 6 hours.
[0051] Example 13 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 13 is the same as the method steps of Example 1, except that in step 1), ODPA and DDS are weighed in a molar ratio of 1.01:1, and after step 3), the polyimide film is taken out and immersed in ethanol for 12 hours, and then dried to obtain a polyimide with high surface electrical strength based on the natural microporous structure of the surface.
[0052] Embodiment 14 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 14 is the same as that of Example 1, except that in step 1), PMDA+BTDA and HMDA are weighed at a molar ratio of 0.99:1, and solvent A is DMF.
[0053] Embodiment 15 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 15 is the same as that of Example 1, except that in step 1), 6FDA and 6F-BAPP are weighed in a molar ratio of 0.99:1, and solvent A is NMP; in step 2), the pore-forming agent is DDAB, and the mass percentage of DDAB is 5%. The mixture is stirred at 1000 rpm for 0.5 h to ensure uniform dispersion of DBP, and a film is coated on a clean glass plate with a scraper.
[0054] Example 16 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 15 is the same as that of Example 1, except that in step 1), 6FDA and IDDA are weighed at a molar ratio of 0.99:1; in step 2), the pore-forming agent is Gly, stirring is performed at 1400 rpm for 0.5 h to ensure uniform dispersion of DBP, and a film is coated on a clean glass plate with a scraper.
[0055] Embodiment 17 A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface comprises the following steps: The preparation method of Example 13 is the same as that of Example 1, except that in step 1), 6FDA and ODA+PDA are weighed at a molar ratio of 0.99:1; in step 2), the pore-forming agent is PEO, and the mass percentage of PEO is 40%. The mixture is stirred at 1200 rpm for 0.5 h to ensure uniform dispersion of DBP, and a film is coated on a clean glass plate with a scraper.
[0056] Comparative Example 1 Comparative Example 1 is a common polyimide film, which is obtained by using the same amount of yellow transparent PAA solution as in Example 1 and directly using a doctor blade of the same height with the aid of a coating machine.
[0057] Experimental example The tensile strength, surface flashover voltage in vacuum, maximum secondary electron emission coefficient and dielectric constant of the high surface dielectric strength polyimide prepared in the above embodiments based on the regulation of the natural microporous structure on the surface were tested using a universal testing machine, a vacuum surface flashover voltage test device, a secondary electron emission coefficient test system and a broadband dielectric spectrum test system. The results are shown in Table 1.
[0058] Table 1 Performance test data of the products obtained in Examples 1-9 and Comparative Example 1
[0059] It can be seen from the data in Table 1 that, compared with ordinary polyimide films, the high surface dielectric strength polyimide based on the regulation of the natural microporous structure on the surface provided by the embodiments of the present invention shows a significantly increased vacuum surface flashover voltage. The vacuum surface flashover performance of Example 1 is most significantly improved, by 43%; Examples 2 and 3 change the content ratio of the pore-forming agent dibutyl phthalate (DBP). When the pore-forming agent content is as low as 10%, it can be seen that the surface of the polyimide film cannot be opened to form through holes. When the pore-forming agent content is 20%, a small number of through holes are formed on the surface, but the size is small. Therefore, the suppression of electron avalanches does not achieve the best effect. When the pore-forming agent content is high, the through holes formed are too large, and the flashover voltage does not increase as a result. It can be seen that the flashover The voltage does not increase with the increase of the size of the surface micropores, and blindly manufacturing large-aperture holes will cause the comprehensive performance of polyimide to decrease; the highest heating temperature of 320°C in Example 4 cannot reach the boiling point and thermal decomposition temperature of the pore-forming agent dibutyl phthalate, so it is impossible to form a microporous structure on the surface of the polyimide, and it is impossible to suppress the development of electron avalanche; the change of the molar ratio of dianhydride diamine in Example 6 and Example 7 will reduce the mechanical properties of the porous film, so the molar ratio of dianhydride diamine is 1.02:1 as the best ratio. In Example 8 and Example 9, since the pore-forming agents used are small-sized pore-forming agents, the apertures of the through holes formed on the surface are all in the order of hundreds of nanometers. The through holes of this size have a certain inhibitory effect on the secondary electron avalanche, and the electrons jumping toward the anode will fall into the through holes during the movement, but due to the small size of the through holes, the probability of electrons being captured is relatively low, so the effect of increasing the flashover voltage is not as significant as in Example 1. In addition, the tensile strength was tested using a universal testing machine. It can be seen from Table 1 that the polyimide prepared from the pure coating in Comparative Example 1 has a very high tensile strength and excellent mechanical and mechanical properties, while the mechanical properties of the polyimide with a natural microporous structure on the surface are slightly reduced, which is due to the presence of the porous structure. However, the mechanical properties have not dropped too low, and the polyimide with a natural microporous structure on the surface can still meet the application of most industrial scenarios. In terms of dielectric constant, the embodiment has a lower dielectric constant than Comparative Example 1, which makes the polyimide with a natural microporous structure on the surface have better results in 5G communications, microelectronics, aerospace and other fields, such as higher signal transmission speed, shorter signal delay time, and lower power consumption.
[0060] The present invention discloses a polyimide with high surface dielectric strength regulated by natural microporous structure on the surface, and a preparation method and application thereof. The polyimide with high surface dielectric strength regulated by natural microporous structure on the surface is prepared by adding pore-forming agent components to a precursor polyamic acid solution, and then performing imidization, high-temperature heating or solvent extraction based chemical methods. The surface of the polyimide has a natural pore structure, and the surface is a surface along the electric field. The through-hole structure of the polyimide along the electric field surface is densely distributed. During the flashover process, electrons easily fall into the through-hole structure during the jump multiplication process, and it is difficult to return to the polyimide surface. Therefore, the secondary electron multiplication process is suppressed, and the probability of forming a secondary electron collapse is reduced, thereby achieving the improvement of the dielectric strength of the polyimide along the surface.
[0061] Each embodiment in this specification is described in a progressive manner, and the same or similar parts between the embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the system embodiment, since it is basically similar to the method embodiment, the description is relatively simple, and the relevant parts can be referred to the partial description of the method embodiment.
[0062] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface, characterized in that: include: The dried diamine is dissolved in solvent A, and then dianhydride is added and stirred to obtain a polyamic acid solution; Then add the pore-forming agent and stir at high speed until it is evenly dispersed to obtain a mixed viscous solution C; After coating, drying, imidization, high-temperature heating, and natural cooling, the film is immersed in liquid B to extract the pore-forming agent, and after drying, a polyimide with high surface electrical strength regulated by the natural microporous structure on the surface is obtained.
2. The method for preparing a polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface according to claim 1, characterized in that: The molar ratio of the dianhydride to the diamine is (0.98-1.05): 1; When adding dianhydride, add it in small amounts and multiple times, with an interval of 15-30 minutes between each addition. Stirring under nitrogen or air atmosphere until a uniform yellow transparent polyamic acid solution is formed; The solid content of the polyamic acid solution is 15-20 wt %.
3. The method for preparing a polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface according to claim 1, characterized in that: The diamine is one or more of 4,4'-diaminodiphenyl ether, p-phenylenediamine, 4,4'-diaminobiphenyl, 2,2'-bis(4-aminophenyl)hexafluoropropane, 4,4'-diaminophenyl sulfone, hexamethylenediamine, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 4,4'-(4,4'-isopropylidene diphenyl-1,1'-diyldioxy)diphenylamine and related derivatives.
4. The method for preparing a polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface according to claim 1, characterized in that: The dianhydride is one or more of pyromellitic dianhydride, 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 4,4'-phenylenedioxydiphthalic anhydride, 4,4'-biphenyl ether dianhydride and related derivatives thereof.
5. The method for preparing a polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface according to claim 1, characterized in that: The solvent A is any one of N,N-dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone; the liquid B is ethanol or ketone; the liquid B can fully dissolve the pore former without destroying or dissolving the polyimide.
6. The method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface according to claim 1, characterized in that: The pore-forming agent is any one of didodecyl dimethyl ammonium bromide, dibutyl phthalate, glycerol, polyethylene glycol, polyethylene oxide and polyhedral oligomeric silsesquioxane; The mass of the pore-forming agent is 5%-40% of the mass of the mixed viscous solution C; When the thermal decomposition temperature of the pore-forming agent is not higher than 440°C, the imidization is heated at high temperature and then cooled naturally to obtain a polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface; When the thermal decomposition temperature of the pore-forming agent is higher than 440°C, the imidization is heated at high temperature, cooled naturally, and then immersed in liquid B to extract the pore-forming agent. After drying, a polyimide with high surface electrical strength based on the natural microporous structure on the surface is obtained.
7. The method for preparing a polyimide with high surface electrical strength based on the regulation of the natural microporous structure on the surface according to claim 1, characterized in that: The high-speed stirring rate is 800-1400 rpm; the high-speed stirring time is 0.5 h.
8. The method for preparing a polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface according to claim 1, characterized in that: The high-temperature heating for imidization adopts a gradient heating and heat preservation method, starting from 80°C, at a heating rate of 5°C / min, heat treatment is performed at intervals of 60°C for 40 minutes, the temperature is raised to 300-450°C, heat treatment is performed for 6 hours, and then cooled to room temperature; if the thermal decomposition temperature of the pore-forming agent is not higher than 440°C, the thermal decomposition temperature of the pore-forming agent plus 10°C is set as the maximum temperature.
9. A polyimide with high surface electrical strength based on the regulation of natural microporous structure on the surface, characterized in that: The polyimide having high surface electrical strength based on the natural microporous structure on the surface is prepared by the preparation method described in any one of claims 1 to 8, and the surface along the electric field is densely covered with micrometer-scale pore structures.
10. Application of high surface electrical strength polyimide based on the regulation of natural surface microporous structure obtained by the preparation method described in any one of claims 1 to 8 in the preparation of insulating components for spacecraft, vacuum circuit breakers, high-energy particle accelerators, pulse power equipment, and semiconductor manufacturing and processing equipment.
Citation Information
Patent Citations
An insulator and a method for improving the electric strength along the surface of the insulator
CN105405545B
Insulator based on 3D printing and preparation method and application thereof
CN115910497A
High-strength high-heat-resistance polyimide microporous thin film and preparation method thereof
CN105778130A
Antistatic atomic oxygen-resistant polyimide film and preparation method thereof
CN116789998A
Preparation method of pore-structure-adjustable polycyclic aromatic hydrocarbon hard carbon and application of pore-structure-adjustable polycyclic aromatic hydrocarbon hard carbon to negative electrode of sodium-ion battery
CN117361490A
Cited By
High-temperature-resistant composite material as well as preparation method and application thereof
CN120081648A